Step-by-Step Method: Can it improve triple jump learning outcomes? - Arifin Arifin; Y. Touvan Juni Samodra; Edi Purnomo (Sriwijaya Journal of Sport, 2022)
The purpose of this study was to find out how many times students could do triple jumps. This research is classroom action research. The subjects in the study were students of class X SMAN 1 Maya Island, with a total of 16 students. The instrument used was the triple jump test. The data analysis technique used in this study was descriptive quantitative. Learning through the step-by-step triple jump is dynamic and fun so that students are active in observing every movement in the triple jump. Based on the research results, namely the initial test, with an average of 51.56 who completed only one student with a score of 6.25%. First cycle, with an average of 66.66, nine students completed with a value of 56.25%. However, the average results from the initial test and first cycle have not reached the expected target. So, it was continued in the second cycle with an average increase of 72.22; 11 students completed with a score of 68.75%. So that the step-by-step learning is successful from 1 student who completes with a score of 6.25% to 68.75%, based on the results of the study, it can be concluded that the increase in triple jump results through step-by-step learning can be seen from the average and completeness results of each student.